Porin channels in Escherichia coli: studies with beta-lactams in intact cells. - Nikaido, H (1983)
Wild-type Escherichia coli K-12 produces two porins, OmpF (protein 1a) and OmpC (protein 1b). In mutants deficient in both of these "normal" porins, secondary mutants that produce a "new" porin, protein PhoE (protein E), are selected for. We determined the properties of the channels produced by each of these porins by measuring the rates of diffusion of various cephalosporins through the outer membrane in strains producing only one porin species. We found that all porin channels retarded the diffusion of more hydrophobic cephalosporins and that with monoanionic cephalosporins a 10-fold increase in the octanol-water partition coefficient of the solute produced a 5- to 6-fold decrease in the rate of penetration. Electrical charges of the solutes had different effects on different channels. Thus, with the normal porins (i.e., OmpF and OmpC proteins) additional negative charge drastically reduced the penetration rate through the channels, whereas additional positive charge significantly accelerated the penetration. In contrast, diffusion through the PhoE channel was unaffected by the presence of an additional negative charge. We hypothesize that the relative exclusion of hydrophobic and negatively charged solutes by normal porin channels is of ecological advantage to E. coli, which must exclude hydrophobic and anionic bile salts in its natural habitat. The properties of the PhoE porin are also consistent with the recent finding (M. Argast and W. Boos, J. Bacteriol. 143:142-150, 1980; J. Tommassen and B. Lugtenberg, J. Bacteriol. 143:151-157, 1980) that its biosynthesis is derepressed by phosphate starvation; the channel may thus act as an emergency pore primarily for the uptake of phosphate and phosphorylated compounds.